2001
DOI: 10.1093/cercor/11.4.360
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between EEG Potentials and Intracellular Activity of Striatal and Cortico-striatal Neurons: an In Vivo Study under Different Anesthetics

Abstract: The functions of the basal ganglia are achieved through excitation of striatal output neurons (SONs) by converging cortical glutamergic afferents. We assessed the relationship between different patterns of activity in cortico-striatal (C-S) cells and the electrical behavior of SONs in vivo. Intracellular activities of rat C-S neurons in the orofacial motor cortex and of SONs, located in the projection field of this cortical region, were recorded under different anesthetics, which generate various temporal patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
125
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 53 publications
33
125
3
Order By: Relevance
“…The firing patterns observed in the striatum in these recordings are consistent with a considerable body of literature which has shown that striatal activity in anesthetized preparations is organized into 'up-states' and 'down-states' by slow, ∼1 Hz oscillations in cortical activity (Wilson and Kawaguchi, 1996;Stern et al, 1997;Mahon et al, 2001;Tseng et al, 2001b;Murer et al, 2002;Goldberg et al, 2003). The increase in spikes per burst in striatal spike trains in the present study in lesioned rats is consistent with an intracellular recording study by Tseng, Murer and colleagues (Tseng et al, 2001b;Murer et al, 2002), which found that a population of striatal neurons is more depolarized after dopamine cell lesion and has an increased probability of firing in the 'up-state', leading to an increased number of spikes per oscillatory cycle.…”
Section: Phase Relationships Of Oscillatory Activity Within the Basalsupporting
confidence: 88%
“…The firing patterns observed in the striatum in these recordings are consistent with a considerable body of literature which has shown that striatal activity in anesthetized preparations is organized into 'up-states' and 'down-states' by slow, ∼1 Hz oscillations in cortical activity (Wilson and Kawaguchi, 1996;Stern et al, 1997;Mahon et al, 2001;Tseng et al, 2001b;Murer et al, 2002;Goldberg et al, 2003). The increase in spikes per burst in striatal spike trains in the present study in lesioned rats is consistent with an intracellular recording study by Tseng, Murer and colleagues (Tseng et al, 2001b;Murer et al, 2002), which found that a population of striatal neurons is more depolarized after dopamine cell lesion and has an increased probability of firing in the 'up-state', leading to an increased number of spikes per oscillatory cycle.…”
Section: Phase Relationships Of Oscillatory Activity Within the Basalsupporting
confidence: 88%
“…Membrane potential of SONs, measured between SWDs, was Ϫ76.8 Ϯ 1.4 mV (n ϭ 10 cells). These membrane properties are similar to those described previously in vivo from nonepileptic rats (Wilson, 1995;Charpier et al, 1999;Mahon et al, 2001Mahon et al, , 2003. This finding suggests that changed neuronal membrane properties did not underlie the inability of GAERS striatal output neurons to fire action potentials during SWDs.…”
Section: Intracellular Activity Of Sonssupporting
confidence: 87%
“…1 A, inset) was characteristic of "regularspiking" neocortical neurons (Connors and Gutnick, 1990). These electrophysiological properties of CS neurons agree with those measured previously in crossed CS neurons from nonepileptic rats (Cowan and Wilson, 1994;Mahon et al, 2001).…”
Section: Intracellular Activity Of Cs Neuronssupporting
confidence: 87%
See 2 more Smart Citations